Kualitas Pura dan Kepuasan Konsumen Pada UD. Sari Murni Desa Sindang Sari Kecamatan Toili Barat Kabupaten Banggai: Quality Temple and Consumer Satisfaction at UD. Sari Murni Sindang Sari Village West Toili District Banggai Regency - Arpan Kurubit; Iim Imaniar (Jurnal Ilmiah Produktif, 2021)
The purpose of this study was to determine whether product quality has a significant effect on customer satisfaction at UD. Sari Murni, Sindang Sari Village, West Toili District, Banggai Regency. The analytical method used in analyzing this research is simple linear regression analysis using 53 samples taken using the Simple Random Samplin technique. Based on the results of research and testing, it is concluded that the quality of temple products has an effect on consumer satisfaction at UD. Sari Murni, Sindang Sari Village, Toili Barat District. While the close relationship between product quality variables and consumer satisfaction variables is in the strong category, and the contribution of product quality variables to consumer satisfaction variables is 44.5%%, while the remaining 55.5% is influenced by other variables not included in the study.